ANALISIS PENYIMPANAN REKAM MEDIS AKTIF RAWAT JALAN GUNA MENINGKATKAN EFEKTIVITAS PELAYANAN DI PUSKESMAS CILENGKRANG KABUPATEN BANDUNG - Febrianti Salawiyah, Febrianti Salawiyah (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2021)
Based on the results of research studies at the Cilengkrang Health Center, Bandung Regency, it is known that in the implementation of the alignment of medical record documents there are still misplaced and missing (misfiles) so that it hinders the process of taking and returning medical record documents both stored and to be borrowed. This misplaced and missing file can affect patient care because it can hamper the examination process, besides that the lost medical record will be regenerated with a new medical record so that the contents of the medical record become ineffective. The purpose of this study was to analyze, to know the description of the lending system on the occurrence of missfiles of outpatient medical record files in the filling room by means of qualitative methods and data collection by interviews, as well as observations at the Cilengkrang Health Center, Bandung Regency. The results showed that from 1,044 outpatient medical record files, 5%, namely 52.2 medical record files, had missfiles, which were not appropriate in placing/compiling medical record files on the proper shelves. Efforts to fix this problem are redesigning the filling room so that the distance between the filling racks is more ergonomic, using tracers and installing procedures / SOPs in the storage room (filling), and using color coding on the folder folder. Keywords : Missfile, Storage, Public Health Center, Medical Record